(untitled) (Qualitative Research Journal for Social Studies, 2026)
This study discusses the relationship of Transhumanism and Afrofuturism and their interplay in the seminal works of Parable of the Sower or Wild Seed by Octavia E. Butler and how these theories integrate with human evolution, racial identity or potential morality in both of these novels. It is a qualitative study that deals with the complex issues of physiological enhancement, socio-political problems and the problem of human agency that is presented in the selected novels. This study examines the Butler challenges the Western patterns of thinking about technological advancement, body sovereignty or racial futures. It explains the ethical possibilities at the intersection of free desire and technology that emphasize collective emancipation as well as the critical connection between technological progress and social justice. The study contributes to the growing literature on the ethical implications of posthuman futures; mapping out the ways the seemingly undercome voices can help to reshape the dominant technology narratives. Overall, the results of the findings indicate that Butler’s works provide a crucial intervention into the primarily white and/or Western transhumanist discourse by focusing on the black experiences and epistemologies in envisioning posthuman futures. Future work could focus on the implications and potential applications of Butler’s holistic perspective on transhumanism and Afrofuturism for discussions on AI ethics, biotechnology governance, and inclusive innovation in the present day.